The influence of Javanese turmeric (Curcuma xanthorrhiza) on the pharmacokinetics of warfarin in rats with single and multiple-dose studies - Taofik Rusdiana; Yanni D. Mardhiani; Norisca A. Putriana; Dolih Gozali; Daisuke Nagano; Takuya Araki; Koujirou Yamamoto (Taylor & Francis Group, 2021)
Context Co-administration between warfarin (WF) and Curcuma xanthorrhiza Roxb. (Zingiberaceae) (CX) is found in Indonesian patients and need to be evaluated. Objective This study assesses the effect of concomitant administration of CX extract on the pharmacokinetics of WF in rats. Materials and methods Wistar rats were divided into 4 groups (n = 6) and administered with 2% Pulvis Gummi Arabicum (PGA, control), fluconazole (FZ, 6 mg/kg), CX-1 (6 mg/kg) or CX-2 (18 mg/kg BW) for 7 days. For the single-dose study, at the 8th day, WF (1 mg/kg) was administered to all groups and blood samples were taken from 0.25 to 72 h. For the multiple-dose study, daily dose of WF was administered to all groups of rats and at the 7th to 9th day, the rats were treated with PGA, CX-1, CX-2 and FZ. Blood samples were withdrawn daily at 4 h after administration of WF from the 1st to 11th day. Results The area under the curve (AUC) of R- and S-WF in the CX-2 group was a significantly higher value compared to the control (77.54 vs. 35.27 mg.h/L for R-WF and 316.26 vs. 40.16 mg.h/L for S-WF; p < 0.05; Kruskal-Wallis method). The CX-2 administration also caused the increasing in the concentration level of R-WF (16%) and S-WF (27%) from the 7th to 9th day of administration. Discussion and Conclusions The CX administration in a higher dose caused alteration on WF pharmacokinetics suggesting the need for clinical evaluation of the interaction between CX and WF.